Sertoli cell tumor and diffuse seminoma in dog with bilateral cryptorchidism - Case report. - Henrique, Fernanda Vieira; Lordão, Fernando Nonato Ferreira; Pessoa, Melquisedeque de Andrade; Carneiro, Rosileide dos Santos (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Henrique F.V., Lordão F.N.F., Pessoa M. de A. & Carneiro R. dos S. [Sertoli cell tumor and diffuse seminoma in dog with bilateral cryptorchidism - Case report.] Tumor de células de sertoli e seminoma difuso em cão com criptorquidismo bilateral - Relato de caso. Revista Brasileira de Medicina Veterinária, 38(3):217-221, 2016. Programa de Pós-Graduação em Medicina Veterinária, Universidade Federal de Campina Grande, Campus de Patos, Rua Dr. José Genuíno, 361, apt. 303, Centro, Patos, Paraíba, Brasil. E-mail: nandinhavh@gmail.com The seminoma and sertoli cell tumor affect commonly older dogs and have low malignancy, with a high incidence in animals with ectopic testes and may coexist in the same individual. This report describes the case of a dog, male, mongrel, nine-year-old, bilateral cryptorchid, who presented abdominal mass, suspected presence of testicular neoplasm. Abdominal ultrasound showed enlarged left testicle and very vascularized. It was performed bilateral orchiectomy. The testes were sent for histopathological evaluation. Microscopic examination of the right testicle revealed a diffuse neoplastic proliferation of germ cells, being diagnosed diffuse seminoma. The left testis showed a neoplastic cellular proliferation forming islands delineated by striking fibrous component characterized as sertoli cell tumor. The animal was re-evaluated again after two months of surgery presenting fully recovered. Testicular neoplasms are common in dogs, with the bilateral orchiectomy the therapy of election.